Flowers into shoots: Photo and hormonal control of a meristem identity switch in Arabidopsis - Okamuro, Jack K. (The National Academy of Sciences of the USA, 1996)
Little is known about the signals that govern the network of meristem and organ identity genes that control flower development. In Arabidopsis, we can induce a heterochronic switch from flower to shoot development, a process known as floral meristem reversion, by manipulating photoperiod in the floral homeotic mutant agamous and in plants heterozygous for the meristem identity gene leafy. The transformation from flower to shoot meristem is suppressed by hy1, a mutation blocking phytochrome activity, by spindly, a mutation that activates basal gibberellin signal transduction in a hormone independent manner, or by the exogenous application of gibberellins. We propose that LFY and AG play an important role in the maintenance of flower meristem identity and that floral meristem reversion in heterozygous lfy and in ag flowers is regulated by a phytochrome and gibberellin signal transduction cascade.